Detection of Trypanosoma cruzi and Trypanosoma rangeli infection in triatomine vectors by amplification of the histone H2A/SIRE and the sno-RNA-C11 genes Detecção da infecção por Trypanosoma cruzi e Trypanosoma rangeli em vetores triatomíneos através da amplificação dos gens de histona H2A/SIRE e sno-RNA-C11 - Paula Ximena Pavia; Gustavo Adolfo Vallejo; Marleny Montilla; Rubén Santiago Nicholls; Concepción Judith Puerta (Revista do Instituto de Medicina Tropical de São Paulo, 2007)
Trypanosoma rangeli is non pathogenic for humans but of important medical and epidemiological interest because it shares vertebrate hosts, insect vectors, reservoirs and geographic areas with T. cruzi, the etiological agent of Chagas disease. Therefore, in this work, we set up two PCR reactions, TcH2AF/R and TrFR2, to distinguish T. cruzi from T. rangeli in mixed infections of vectors based on amplification of the histone H2A/SIRE and the small nucleolar RNA Cl1 genes, respectively. Both PCRs were able to appropriately detect all T. cruzi or T. rangeli experimentally infected-triatomines, as well as the S35/S36 PCR which amplifies the variable region of minicircle kDNA of T. cruzi. In mixed infections, whereas T. cruzi DNA was amplified in 100% of samples with TcH2AF/R and S35/S36 PCRs, T. rangeli was detected in 71% with TrF/R2 and in 6% with S35/S36. In a group of Rhodnius colombiensis collected from Coyaima (Colombia), T. cruzi was identified in 100% with both PCRs and T. rangeli in 14% with TrF/R2 and 10% with S35/S36 PCR. These results show that TcH2AF/R and TrF/R2 PCRs which are capable of recognizing all T. cruzi and T. rangeli strains and lineages could be useful for diagnosis as well as for epidemiological field studies of T. cruzi and T. rangeli vector infections. Embora o Trypanosoma rangeli não seja patogênico para o homem, sua importância médica e epidemiológica reside no fato de compartilhar vetores, reservatórios e áreas geográficas com o Trypanosoma cruzi, agente causal da Doença de Chagas. Neste estudo, para distinguir T. cruzi de T. rangeli em vetores com infecções mistas, se utilizaram duas amplificações de PCR; TcH2AF/R para o gen da histona H2A/SIRE e TrFR2, para um gen repetitivo de ARN nucleolar Cl1 (sno-RNA-Cl1). Assim como a PCR S35/S36, ambas as reações foram capazes de detectar corretamente a presença de T. cruzi ou T. rangeli em triatomíneos infectados experimentalmente. Nas infecções mistas, o ADN de T. cruzi foi amplificado em 100% das amostras quando se utilizaram TcH2AF/R e ...